2016
DOI: 10.1038/ejhg.2016.146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical exome sequencing: results from 2819 samples reflecting 1000 families

Abstract: We report our results of 1000 diagnostic WES cases based on 2819 sequenced samples from 54 countries with a wide phenotypic spectrum. Clinical information given by the requesting physicians was translated to HPO terms. WES processes were performed according to standardized settings. We identified the underlying pathogenic or likely pathogenic variants in 307 families (30.7%). In further 253 families (25.3%) a variant of unknown significance, possibly explaining the clinical symptoms of the index patient was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
239
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(264 citation statements)
references
References 38 publications
22
239
1
2
Order By: Relevance
“…Trujillano et al (2017) reported a single patient with febrile seizures and epilepsy with a de novo SCN3A p.Pro1333Leu mutation, which is the same mutation seen in Patient 3 in our study, although additional details regarding the patient phenotype were not provided. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Trujillano et al (2017) reported a single patient with febrile seizures and epilepsy with a de novo SCN3A p.Pro1333Leu mutation, which is the same mutation seen in Patient 3 in our study, although additional details regarding the patient phenotype were not provided. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Three diagnostic WES trio cohorts reported 8051 patients with neurodevelopmental disorders (defined as human phenotype ontology terms (1) abnormality of the nervous system, (2) multiple congenital anomalies, (3) seizures or (4) ASD. 2022 Overall, 15 pathogenic/likely pathogenic GRIN2B variants (14 missense, 1 frameshift) were identified, equalling a similar frequency of 0.19%. Expanding the data of the Deciphering Developmental Disorders Study, 23 14 de novo missense variants in GRIN2B are significantly enriched (p value 2×10 −17 ) in a combined cohort of WES trio data (n=8051) of patients with neurodevelopmental disorders (see online supplement 3).…”
Section: Resultsmentioning
confidence: 97%
“…In another study, more complex phenotype has been noted to yield a higher diagnosis rate comparing to isolated phenotype. 25 Further studies in larger sample size are needed to corroborate these data for selecting infants most likely to benefit from exome sequencing in ICUs.…”
Section: Discussionmentioning
confidence: 99%